Numerical investigation of the baffle plates effect on the solar water storage tank efficiency. Issue 16 (17th August 2020) - Samet, A.; Ben Souf, M. A.; Fakhfakh, T.; Haddar, M.
ABSTRACT: This paper presents a numerical research of the influence of baffle plates integration inside a horizontal storage tank on the solar water storage tank efficiency. In this work, the baffle plates are integrated inside the tank with different locations and different distances between them to study their effects and also to determine the optimum position in order to enhance the thermal storage system (TSS) performance. The CFD comparison between all proposed designs was carried out and different methods of evaluating mixing and stratification such as temperature evolution, outlet temperature, Richardson number, and full efficiency were calculated to quantify the degree of stratification. Results show that the TSS performance depends on the baffle locations and distance between them. Therefore, a superior thermal performance was achieved for baffles with superior distance between them which are maintained in top of the water storage tank (WST).